Evaluasi Dan Perancangan Antarmuka Aplikasi Pelayanan Kesehatan Mobile Bagi Lansia - Amy Hewu Hawini; Restyandito Restyandito; Danny Sebastian (Fakultas Teknologi Informasi, 2022)
The interface is a very important thing for a system or application, because it connects users directly with technology. An easy interface makes users skilled when using a system or application, especially for the elderly so as not to become a marginalized group in the technology era. mobile JKN is an application developed and managed by the government that focuses on public services, namely BPJS which is converted from a system of administrative activities carried out at branch or central offices into an application. This study focuses on designing the JKN mo-bile application interface for the elderly with a case study that refers to the JKN v2.11.0 mobile application interface, where based on usability results that have been carried out for the elderly, mobile JKN is not yet user friendly such as the interface is too complex, icons and writing that is too small, and navigation in depth so that the application interface is not optimal for the elderly. Therefore, recommendations for the design of the JKN mobile application interface were made according to the characteristics of the elderly using expert guidelines so as to produce an interface with gridview and listview menu layout with dropdowns; bold and capital letters with sizes 16 and 20 sp; using 3-dimensional icons with 90 dp cardview description. Usability testing used in this study uses the principles of ISO 9241-11. The result showed a significant increase for effectiveness, efficiency as well as satisfaction.